THE USE OF SERIES OF PICTURES TO IMPROVE STUDENTS' ABILITY IN WRITING RECOUNT TEXT:A Quasi-Experimental Research at One Senior High School in Bandung - Yulia Purnamasari, - (2012)
The research entitled The Use of Series of Pictures to Improve Students' Ability in Writing Recount Text was to investigate whether or not the use of series of pictures was effective in teaching recount writing text. It was also aimed to investigate the students' responses to the use of series of pictures in teaching writing recount text. This research employed quasi-experimental design. This research was done in the tenth grade of a senior high school in Bandung. Two classes of the students were selected to be the samples of this research, one class as the control group and one class as the experimental group. Then, the data were obtained through a pre-test, post-test andquestionnaire. The data gathered through pre-test and post-test computed one by one using IBM SPSS Statistics 19.0 for Windows while the data from questionnaire were analyzed based on the frequency of the students' answers and then calculated,made inpercentages, and interpreted. The research findings showed that the experimental group had higher writing score. The statistical computation showed that the use of series of pictures are effective in improving the students' recount writing (tobt >tcrit, 3.912 > 2.052, r = 0.558). Moreover, the data from questionnaire showed that the use of series of pictures waspositively responded by the students. Based on these findings, it is recommended that series of pictures are applied in teaching writing.